Effects of Bougainvillea glabra leaf on growth, skin mucosal immune responses, and disease resistance in common carp Cyprinus carpio. Issue 132 (January 2023) - Giri, Sib Sankar; Kim, Sang Guen; Woo, Kang Jeong; Jung, Won Joon; Lee, Sung Bin; Lee, Young Min; Jo, Su Jin; Hwang, Mae Hyun; Park, JaeHong; Kim, Ji Hyung; V, Sukumaran; Park, Se Chang
Abstract: This study evaluated the effects of Bougainvillea glabra (BG) leaf as a feed supplement on growth, skin mucosal immune parameters, serum oxidative stress, expression of immune-related genes, and susceptibility to pathogen infection in carp Cyprinus carpio . Diets containing four different BG concentrations (g kg −1 ), i.e., 0 g (basal diet), 20 g (BG20), 30 g (BG30), 40 g (BG40), and 50 g (BG50), were fed to the carp (average weight: 14.03 ± 0.81 g) for 8 weeks. Skin mucosal immunological and serum antioxidant parameters were examined 8 weeks post-feeding. Growth performance was significantly higher in BG40. Among the examined skin mucosal immune parameters, lysozyme (33.79 ± 0.98 U mL −1 ), protein (6.88 ± 0.37 mg mL −1 ), immunoglobulin (IgM; 5.34 ± 0.37 unit-mg mL −1 ), and protease activity (3.18 ± 0.36%) were significantly higher in BG40 than in the control; whereas, there was no significant effect on the alkaline phosphatase level. Among serum immune activity, activities of lysozyme, the alternative complement pathway, and IgM were significantly higher in BG40. Phagocytic, and superoxide dismutase (SOD) activities were higher ( P  < 0.05) in BG30–BG50. Serum ALT, AST, and MDA levels were lower in BG40 than in the control ( P  < 0.05). Intestinal enzymatic activities were enhanced in BG40 and BG50 ( P  < 0.05), except for lipase in BG50. Gene expression analysis revealed that the mRNA expressions of antioxidant genes ( SOD, GPx, and Nrf2 ), an anti-inflammatory gene ( IL-10 ), and IκBα were significantly upregulated in BG40. Conversely, the pro-inflammatory gene IL-1β and the signaling molecule NF-κB p65 were downregulated in BG40 and BG50, respectively. BG supplementation had no significant effect on TNF-α, TLR22, or HSP7 0 mRNA expressions . Moreover, fish in BG40 exhibited the highest relative post-challenge survival (67.74%) against Aeromonas hydrophila infection. These results suggested that dietary supplementation with BG leaves at 40 g/kg can significantly improve the growth performance, immune responses, and disease resistance of C. carpio . BG leaves are a promising food additive for carp in aquaculture. Highlights: Dietary Bougainvillea glabra leaf improves the growth performance in Cyprinus carpio. B. glabra supplementation increased the growth, anti-oxidant status, and immune responses of fish. B. glabra at 40 g/Kg provided significant protection against Aeromonas hydrophila challenge. Dietary supplementation with 40 g/kg B . glabra leaves showed significant benefits.